Increases in apoptosis, caspase activity and expression of p53 and bax, and the transition between two types of mitochondrion-rich cells, in the gills of the climbing perch, Anabas testudineus, during a progressive acclimation from freshwater to seawater - Ching, B. (2014)
10.3389/fphys.2013.00135